2012
DOI: 10.4103/2230-8210.105576
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fat mass and obesity-associated gene variants on the body mass index among ethnic groups and in children and adults

Abstract: Genome-wide association analyses have revealed common gene variations related to obesity. Variants of the fat mass and obesity-associated (FTO) gene among more than 40 genes studied were most closely associated with obesity, but the association varies among ethnicities. Moreover, the effect is significant in people of European descent as well as Asians, but less significant among people of African descent. Although the variants were also associated with type 2 diabetes and glucose homeostasis, the associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…The instrument was significantly associated with ethnicity ( p < 0.001), which suggests a possible violation of the independence assumption by population stratification, which occurs when alleles occur with different frequencies in a population subgroup [ 22 ]. This finding is consistent with previous genetic studies that have shown varying effect sizes for obesity-related genes among different ethnicities [ 45 , 46 ]. However, there was no significant association of ethnicity with inpatient healthcare cost ( p = 0.896).…”
Section: Resultssupporting
confidence: 93%
“…The instrument was significantly associated with ethnicity ( p < 0.001), which suggests a possible violation of the independence assumption by population stratification, which occurs when alleles occur with different frequencies in a population subgroup [ 22 ]. This finding is consistent with previous genetic studies that have shown varying effect sizes for obesity-related genes among different ethnicities [ 45 , 46 ]. However, there was no significant association of ethnicity with inpatient healthcare cost ( p = 0.896).…”
Section: Resultssupporting
confidence: 93%
“…The FTO gene is the first and most robustly replicated gene that is related to body weight and fat mass [ 32 , 33 ]. However, the underlying mechanisms remain to be unclear.…”
Section: Discussionmentioning
confidence: 99%